HIDAYAT AL SALIKIN (Analisa Hadis Dalam MempengaruhiBudaya Melayu Palembang) - Sulaiman Mohammad Nur (JIA (Jurnal Ilmu Agama), 2016)
Shaykh 'Abd al-Samad al Falembaniy is scholar who also have a role to spread Islam in the archipelago. In order to combat irregularities and practice of religious teachings in the archipelago, he translated two works of al Ghazaliy‟s, Lubab Ihya 'Ulum al-Din and al Bidayat Hidayat. Two of these works present a system of Sufism at that time. Al Falembaniy also authored many books of Sufism, one of his works entitled Hidayat al Salikin. His contribution in Islamic thought has shown how his works have been "transmitted" to become a tradition of Islam in Malay Archipelago. Hadis on meal at the dawn of fasting day in Hidayat al Salikin explain how, the meal can distinguish between the fasting of Muslims and that of non Muslims. Furthermore, the meal will give the blessing. It is Prophet Muhammad tradition, and it provides motivation in worship. Hadith about the efficacy of zam-zam water is written in Hidayat al Salikin book. Ite explains how the zam zam contains a lot of vapour chemical elements that are not found in other water. It also provides motivation in public health. Hadith about the dreams is also written in his book Hidayat al Salikin. It explains how the forecast on dreams that exist in the community is wrong. Then it turns on explaining how the actual nature of dreams.